Effects of feeding spraydried bacteriocin of Lactococcus lactis subsp. Lactis-RW18 in postweaning rats - Hairul Anuar Harun.
None information was available on the effects of using spraydried metabolites of Lactococcus spp. isolated from our local fermented food, 'tapai ubi'. Thus, this study aimed to investigate the effects of feeding spraydried bacteriocin, produced by lactic acid bacteria on faecal pH, Enterobacteriaceae bacterial and LAB counts in faeces, plasma cholesterol concentration and growth performance of postweaning rats treated with different levels of spraydried bacteriocin as additive in basal diet. A total of fifteen 4 weeks old Spague dawley (male) rats, were housed individually in each cage for each treatment. The rats were weighed weekly for four weeks. Water and feed were supplied ad-libitum and feed intake was measured daily and provided in mash form. The animals were randomly assigned to three groups: (i) basal diet (as control); (ii) 99.75% (w/w) basal diet + 0.25% (w/w) spraydried bacteriocin from L. lactis subsp. lactis- RW18; (III) 99.5% (w/w) basal diet + 0.50% (w/w) spraydried bacteriocin from L. lactis subsp. lactis- RW18. All groups were acclimatized to the respective diets for one week before the experiment started. The present study showed that the 0.25% spraydried bacteriocin group had the best performance compared to the 0.50% and control groups on growth performance, faecal LAB and Enterobacteriaceae counts, faecal pH and plasma cholesterol concentration.